Rajasthani Kathputli: Livelihood Generation through Creative Economy - Gupta, Shikha (Prabandhan: Indian Journal of Management, 2019)
The Rajasthani kathputli making is one of the heritage arts and is a part of Rajasthan’s rich culture. It still carries the legacy to produce handcrafted kathputlis. At different stages, there are lots of people involved in the kathputli making process. The study revealed that even though there is demand for kathputlis, the economic status of artisans is poor as the market is unorganized. The study assessed the financial supply chain of Rajasthani kathputli making. The study also looked into the problems and solutions. The study contributed to the value chain analysis of the dying art of Kathputli making.